ChemInform Abstract: Deuterium NMR Investigations of Field‐Induced Director Alignment in Nematic Liquid Crystals. Issue 34 (4th August 2016) - Sugimura, Akihiko; Luckhurst, Geoffrey R.
Abstract: Review: 89 refs.